Procédures pour infliger des sanctions disciplinaires au travailleur selon la loi irakienne du travail n ° (37) de 2015 (une étude comparative avec les lois du travail en Algérie, aux Émirats arabes unis et en France - Abbass, Manal; Noaman, Saba (Journal of Legal Sciences, 2022)
The procedures for imposing disciplinary sanction against the worker represent the steps that must be followed to verify the violation attributed to the worker in preparation for taking the decision to impose disciplinary sanction on him in terms of the procedures for carrying it out, i.e. from the moment of the disciplinary violation until the judgment thereof, as well as the rights, obligations and legal ties resulting from these procedures, These procedures are governed by multiple and dispersed rules, and they aim in their entirety to control the discipline process and determine its course by adhering to the restrictions stated in the law that regulate the process of imposing them, and perhaps one of the most important of these procedures, which in themselves constitute the most effective guarantee for protecting the worker, is the need to specify the penalties and violations in a written disciplinary rules, and the imposition of the penalty on the violating worker should be preceded by confronting the worker with the charges against him, as well as conducting an investigation with him and hearing his defense in compliance with the principle of the right of the accused worker to defend himself and to ensure that the disciplinary sanction is justified.